Exploring TQM awareness in the Greek national business context: between conservatism and reformism cultural determinants of TQM - Alexandros Psychogios; Adrian Wilkinson (2007)
This paper develops the theoretical understanding of the application of Total Quality Management (TQM) in business environments that differ from those from where it emerged. Business systems that are less developed tend to adopt more ‘sophisticated’ and formal strategic initiatives. The adoption of TQM by Greek organizations is a prime example. However, less has been said about the understanding of TQM or its cultural determinants in such environments. This paper, based on the results of 73 semi-structured interviews conducted with managers working in Greek public and private organizations, argues that there are two antithetical business-cultural ‘forces’ – conservatism and reformism – that seem to substantially affect the awareness and application of total quality concepts. Both features create pressures in the system, either restraining or promoting TQM implementation. In this context, the tension between traditional business culture and a modernization logic is the key to understanding the development of TQM.